O movimento de mulheres em interlocução com o Governo Federal na construção de políticas para mulheres no Brasil (2002-2006) - Rocha, Maria Beatriz Pires da (2009)
During the whole of history, women have been supporting the most general struggles, also looking for answers for their specific demands. In Brazil, the women s movement has been recognized due to its capacity in trying to build consensus strategies within the diversity of its organizations and networks in important periods of the political history of the country, in order to be able to strengthen with it its position in the opposition or negotiation with the State. The objective of the research was to establish the relationship of the social movement with the government in terms of gender issues in public policies, reflecting the women s movement as a collective subject in the construction of the proposal for a popular political project. We defined as object those actions from the Lula government through the Special Secretariat for Women s Policies (SPM) that have come true through policies for women after the implementation of the I National Plan for Women s Policies (PNPM) in 2005. This is a social qualitative research which has been organized in three different phases: the first one was the bibliographical and documental research; the second was the field research with interviews with representatives of the government and the women s movement, and, finally, the third one, the systematization and the research analysis. The research revealed that the creation of a body like a SPM and the I PNPM were crucial in order to progress in public policies and programmers for women, recognizing that the construction of those policies is a process disputed by different political projects in society where the studies of the relationship between the government and the movement, and of the latter with its grassroots reveals a lot about the space occupied by women in the political stage and about the progress achieved